Strengthening the Character of Caring for the Environment in Elementary Schools through Ecoprint Artwork - Nugroho, Arief Setyo; Sumardjoko, Bambang; Desstya, Anatri; Minsih; Choiriyah (Universitas Pendidikan Ganesha, 2023)
Technological developments have an impact on decreasing environmental quality. Conditions show that there are a lot of plants in the school garden that are not well cared for, trash used for food and drink packaging is left scattered. There has been a lot of research on strengthening the character of caring for the environment but it is still limited to the substance of learning and on school cleaning activities. The purpose of this study was to analyze the results of strengthening the character of caring for the environment through ecoprint artwork in elementary schools. To reveal the problems in research using a qualitative descriptive approach. For data collection needs, the types of instruments used are interviews and observations. Researchers use triangulation techniques and sources to test the validity of the data. Research an this is done using interactive data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that the implementation of strengthening the character of caring for the environment through ecoprint artwork in elementary schools in general, it can be concluded that strengthening the character of caring for the environment through ecoprint artwork has a success percentage of 88.32%. Apart from the main goal of strengthening the character of caring for the environment, it has another impact, namely being able to awaken the entrepreneurial spirit of students by producing paintings and cloth products with leaf motifs that can have economic selling value.